Turquois - Pogue, Joseph E. (Rio Grande Press Glorieta, New Mexico, 1972)
If ever there was a book with an all inclusive title, this is it: the book contains everything you might want to know about Turquoise. Contains a huge list of Mines and Prospects, with locations. Eighteen full-page color plates. A history of turquoise, with mineralogy, occurrence, origin and uses. Nicely bound in leather-look embossed light green cover, with titles and decorations in color.
39200
Keywords: Southwest; Turquoise